Improving Civics Learning Outcomes through the Cooperative Learning Model Teams Games Tournament among Fourth Grade Students at Tiakur Elementary School - Makay, Daniel Erwin; Rumtutuly, Fransheine; Ritiauw, Leonid (Honoli of Journal Primary Teacher Education, 2025)
This study aims to improve the learning outcomes of Civics students of grade IV of Tiakur State Elementary School through the Teams Games Tournament cooperative learning model. This classroom action research involved 30 students with data collection techniques through observation and written tests. The results showed a significant increase from cycle I to cycle II, where the percentage of students achieving scores above the KKM increased from 32.14% to 100%, with an average final score of 76.66. The application of the Teams Games Tournament model has proven effective in creating an interactive and enjoyable learning atmosphere, so that it can improve student learning outcomes.